ISYARAT ONTOLOGIS INTEGRASI ILMU PENGETAHUAN; (Sebuah Kajian filsafat terhadap Teks Hadits Siksa Kubur) - M.Ag., Dr.Fuady Anwar, (Menara Ilmu, 2016)
This article will discuss regard to the ontology cues of science integration. It isdiscovered in the hadith (tradition) of prophet Muhammad S.A.W. talked about themistreatment of grave. Meanwhile, to reveal this article date is used the philosophyapproach.Then, as for the result of this discussing, there was two points the prophetMuhammad’s message for his members (ummah) so they get the cultivation both in the earthand the hereafter. Firstly,always take care the self-cleanness.And secondly,to develop theIslamic education through the science integration. In other word we are charged to apply thetwo directions above by enforcement the Islamic education equally between the Islamic studies(ushul al-ad-diin) and the secular sciences. And the same time take care the self-cleanness inspirituality and bodily.Keyword: ontology cues,science integration.